Religious Education as a Tool for Mental Health Improvement in Madrasah Aliyah - Khodijah, Ajeng; Nani, Irvan; Rahmat, Munawar (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study aims to analyze and describe the role of religious education in improving the mental health of Madrasah Aliyah students. A meta-analytic approach was employed to identify patterns and commonalities from various previous studies to explore the relationship between religious education and mental health. This analysis synthesized findings from multiple sources to provide a comprehensive understanding of how religious education can affect students' psychological well-being. This study found that well-designed and effectively implemented religious education has significant potential to help students manage stress and improve psychological health. Religious education not only provides a framework of values and norms that help students deal with various emotional challenges, but also strengthens spiritual aspects that can help improve overall mental health. The findings highlight the importance of integrating spiritual aspects into the madrasa curriculum as a strategy to improve students' mental health. This study is expected to provide useful recommendations for educators and policy makers in designing and implementing more effective religious education programs, with the ultimate goal of supporting the psychological health of Madrasah Aliyah students